Balega Dalam Rami - Farras Annafi; Wimbrayardi Wimbrayardi (Universitas Palangka Raya, 2024)
This artwork aims to interpret the phenomenon and behavior of the community at the baralek event starting from the preparation stage to the party stage equipped with the art of saluang bagurau into a new musical composition. The process of creating this artwork is carried out with the observation (exploration), experimentation (improvisation), and forming stages. The idea of the musical work